The African concept of caring for life - Masango, Maake (HTS teologiese studies, 2005)
This article analyses the village concept of caring among African people. The old pattern of caring was based on the concept of ubuntu (humanity) which respects people, because they are created in the imago Dei. Then the article compares the western concept of caring, which is based on individualism and people's privacy. Finally, economy, globalisation and this western concept are analysed. The impact of the above concepts affects Africans in urban areas, who are caught up in the two worlds, namely the African and western worlds.